Cost-effectiveness of natalizumab vs fingolimod for the treatment of relapsing-remitting multiple sclerosis: analyses in Sweden. (April 2015) - O'Day, Ken; Meyer, Kellie; Stafkey-Mailey, Dana; Watson, Crystal
Abstract Objective: To assess the cost-effectiveness of natalizumab vs fingolimod over 2 years in relapsing-remitting multiple sclerosis (RRMS) patients and patients with rapidly evolving severe disease in Sweden. Methods: A decision analytic model was developed to estimate the incremental cost per relapse avoided of natalizumab and fingolimod from the perspective of the Swedish healthcare system. Modeled 2-year costs in Swedish kronor of treating RRMS patients included drug acquisition costs, administration and monitoring costs, and costs of treating MS relapses. Effectiveness was measured in terms of MS relapses avoided using data from the AFFIRM and FREEDOMS trials for all patients with RRMS and from post-hoc sub-group analyses for patients with rapidly evolving severe disease. Probabilistic sensitivity analyses were conducted to assess uncertainty. Results: The analysis showed that, in all patients with MS, treatment with fingolimod costs less (440, 463 Kr vs 444, 324 Kr), but treatment with natalizumab results in more relapses avoided (0.74 vs 0.59), resulting in an incremental cost-effectiveness ratio (ICER) of 25, 448 Kr per relapse avoided. In patients with rapidly evolving severe disease, natalizumab dominated fingolimod. Results of the sensitivity analysis demonstrate the robustness of the model results. At a willingness-to-pay (WTP) threshold of 500, 000 Kr per relapse avoided, natalizumab is cost-effective in >80% of simulations in both patient populations. Limitations: Limitations include absence of data from direct head-to-head studies comparing natalizumab and fingolimod, use of relapse rate reduction rather than sustained disability progression as the primary model outcome, assumption of 100% adherence to MS treatment, and exclusion of adverse event costs in the model. Conclusions: Natalizumab remains a cost-effective treatment option for patients with MS in Sweden. In the RRMS patient population, the incremental cost per relapse avoided is well below a 500, 000 Kr WTP threshold per relapse avoided. In the rapidly evolving severe disease patient population, natalizumab dominates fingolimod.